An Approach to Periarthritis of Shoulder Joint an Ayurvedic Perspective (International Journal of Ayurveda and Pharma Research, 2023)
Periarthritis of the shoulder is a painful, progressive, and disabling disease involving the shoulder joint. The structures involved in the disease are joint capsule, tendons, ligaments, and bursae. As the shoulder movements are painful, the disease makes homemakers, software professionals, skilled workers, manual labourers, and athletes’ lives miserable. The patients were unable to do routine activities like combing hair, dressing, undressing, and doing overhead activities. The initial stages of the disease can be correlated with features of Amsa sandhi sopha having Raktha pitha predominance. The procedures like Lepanam, Upanaham, and internal medications adopted in this stage do not give permanent and complete relief from symptoms. Jaloukavacharana (leech therapy) is selected in the present study by considering the Dosha vitiation - in the initial stages of the disease, as it has anti-inflammatory and analgesic effects. Three Jaloukas (leeches) are applied at a time with intervals of three weeks over the glenohumeral joint (shoulder joint). Assessments were done before treatment, 8th, 15th and 22nd days. The results showed Jaloukavacharana was effective in the first stage of the disease.